2010
DOI: 10.1007/s00442-010-1846-3
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing responses of dragonfly species richness to area, nutrients, water plant diversity and forestry

Abstract: Understanding large-scale variation in species richness in relation to area, energy, habitat heterogeneity and anthropogenic disturbance has been a major task in ecology. Ultimately, variation in species richness results from variation in individual species occupancies. We studied whether the individual species occupancy patterns are determined by the same candidate factors as total species richness. We sampled 26 boreal forest ponds for dragonflies (Odonata) and studied the effects of shoreline length, water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 29 publications
0
23
2
Order By: Relevance
“…The sedentary habitat specialist C. mercuriale (Rouquette and Thompson 2004, Watts et al 2004b showed the lowest level of gene flow and the strongest genetic substructuring, where an impact of the Pyrenees was traceable in patterns of both substructuring and gene migration. Coenagrion pulchellum is the largest and most widespread of the species in this study, it is considered a dispersal prone habitat generalist (similar to C. puella) but it exists in lower local abundances than for example C. johanssoni (Honkanen et al 2011) and C. puella (Conrad et al 1999). The two northern species, C. armatum and C. johanssoni were similar in levels of gene flow.…”
Section: Genetic Diversity and Differentiationmentioning
confidence: 75%
See 1 more Smart Citation
“…The sedentary habitat specialist C. mercuriale (Rouquette and Thompson 2004, Watts et al 2004b showed the lowest level of gene flow and the strongest genetic substructuring, where an impact of the Pyrenees was traceable in patterns of both substructuring and gene migration. Coenagrion pulchellum is the largest and most widespread of the species in this study, it is considered a dispersal prone habitat generalist (similar to C. puella) but it exists in lower local abundances than for example C. johanssoni (Honkanen et al 2011) and C. puella (Conrad et al 1999). The two northern species, C. armatum and C. johanssoni were similar in levels of gene flow.…”
Section: Genetic Diversity and Differentiationmentioning
confidence: 75%
“…Most enigmatic was C. pulchellum, with relatively low levels of gene flow and complicated population substructuring. Coenagrion pulchellum is the largest and most widespread of the species in this study, it is considered a dispersal prone habitat generalist (similar to C. puella) but it exists in lower local abundances than for example C. johanssoni (Honkanen et al 2011) and C. puella (Conrad et al 1999). Finally, when comparing across species, there were again no strong general trends emerging, for example, the largest and the smallest species had the strongest substructuring (C. pulchellum and C. mercuriale, respectively), the sampled ranges of the two largest species, C. pulchellum and C. puella differed by very little, yet their overall genetic differentiation levels (based on F ST values) and patterns of substructure were very different.…”
Section: Genetic Diversity and Differentiationmentioning
confidence: 93%
“…Since then, several studies have formally used this approach (e.g. see Krasnov et al, 2010;Honkanen et al, 2011;Azeria et al, 2011; for recent studies). In general, these studies start with very large taxonomic groups (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to water quality drainage results in inevitable changes in vegetation patterns [12,15]. This may affect Odonata as they use vegetation for multiple purposes such as for hunting or shelter [37], and a positive relationship between Odonata and plant species richness have been found at multiple spatial scales [38-40]. However, the fact that in some sites Odonata species respond rapidly to restoration suggests that vegetation patterns are not at least the main reason for diminished abundance in drained sites as the response of vegetation to restoration are generally rather slow [11,16,19].…”
Section: Discussionmentioning
confidence: 99%